2016
DOI: 10.1371/journal.pone.0161876
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Next Generation Sequencing and EPR Analysis to Uncover Molecular Mechanism Underlying Shell Color Variation in Scallops

Abstract: The Yesso scallop Patinopecten yessoensis displays polymorphism in shell colors, which is of great interest for the scallop industry. To identify genes involved in the shell coloration, in the present study, we investigate the transcriptome differences by Illumina digital gene expression (DGE) analysis in two extreme color phenotypes, Red and White. Illumina sequencing yields a total of 62,715,364 clean sequence reads, and more than 85% reads are mapped into our previously sequenced transcriptome. There are 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 63 publications
(101 reference statements)
0
8
0
Order By: Relevance
“…At present, the main shell pigments found in Mollusca are carotenoids, melanin and tetrapyrroles, including porphyrins and bile pigments 11 , 18 . The molecular processes involved in the synthesis of pigment have been studied in only a few molluscs 19 24 . Of that, the regulatory mechanism for melanin synthesis is better known in cephalopods, involving in the activation of tyrosinase and increased melanin synthesis in the ink gland 25 .…”
Section: Introductionmentioning
confidence: 99%
“…At present, the main shell pigments found in Mollusca are carotenoids, melanin and tetrapyrroles, including porphyrins and bile pigments 11 , 18 . The molecular processes involved in the synthesis of pigment have been studied in only a few molluscs 19 24 . Of that, the regulatory mechanism for melanin synthesis is better known in cephalopods, involving in the activation of tyrosinase and increased melanin synthesis in the ink gland 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Our current knowledge on muscle specific proteins in scallops has been established primarily by traditional biochemical and immunohistochemical techniques, which require laborious work and yield a limited number of enzymes or proteins [ 10 ]. Recently, the advances in iTRAQ (isobaric tags for relative and absolute quantitation) proteomics and RNA-Seq transcriptomics enable us to identify and quantify thousands of genes and proteins in a single experiment [ 3 , 29 31 ]. Here, we performed the first, integrated proteomic and transcriptomic analyses of differences between the fast (striated) and slow (catch) adductor muscles in Yesso scallop ( Patinopecten yessoensis ; Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, transcriptomes and digital gene expression analysis of four different color clams, Meretrix meretrix, suggested that several potential genes and the Notch pathway played a crucial role in its shell color patterning (Yue et al, 2015). The same method was also exerted in two extreme color phenotypes of Yesso scallop, Patinopecten yessoensis, and 25 significantly differential expression genes were identified for unraveling shell color differences (Sun et al, 2016). These researches provided pivotal loci/genes responsible for the formation of shell coloration and served as candidate markers for mollusks breeding projects.…”
Section: Introductionmentioning
confidence: 96%